Concomitant follicular lymphoma and histiocytic sarcoma: A rare progression, trans-differentiation or co-occurrence? - Anuj Verma; Tanuja Shet (Wolters Kluwer Medknow Publications, 2015)
Trans-differentiation of follicular lymphoma (FL) into a histiocytic sarcoma (HS) is a rare event and usually occurs as a sequential event. We report a case where in the same node with two distinct areas one of low-grade FL and another with HS was observed. This patient was a 58 years old with generalized lymphadenopathy and Ann Arbor Stage III disease. The cervical node biopsy on histological examination revealed two distinct areas, firstly a FL with nodular architecture and the other a smaller focus of sheets of pleomorphic histiocytic cells diffusely arranged at the edge of the section contiguous with FL with few cells in transiting phase. On immunohistochemistry the FL was positive for CD20, CD10, PU.1, PAX5 and Bcl2, while the large histiocytic cells were positive for CD163, CD68, LCA, and PU.1, weakly for PAX5 and negative for CD20, CD10, CD30, CD3, CD1a, Bcl2, S100, and Alk-1. The therapeutic implications of this diagnosis and postulated theories on trans-differentiation are discussed.